2021
DOI: 10.3390/polym13223935
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Waste Glass and the Effect of Process Parameters on the Properties of Sustainable Cement and Geopolymer Concrete—A State-of-the-Art Review

Abstract: Recent research has revealed the promising potential of using waste glass (WG) as a binder or inert filler in cement and geopolymer concrete to deliver economic and environmental benefits to the construction sector. However, the outcomes obtained by different research groups are scattered and difficult to compare directly because of isolated process parameters. In this study, the roles and impacts of WG and process parameters on the performance of WG-added cement and geopolymer concrete are critically reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 129 publications
(336 reference statements)
1
8
0
Order By: Relevance
“…Recently the use of recycled polymers in geopolymer concrete has been under investigation [ 40 ]. Abousnina et al [ 41 ] added short fibers, including polypropylene fibers, to enhance the mechanical properties of geopolymer mortar containing fine oil-contaminated sand.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the use of recycled polymers in geopolymer concrete has been under investigation [ 40 ]. Abousnina et al [ 41 ] added short fibers, including polypropylene fibers, to enhance the mechanical properties of geopolymer mortar containing fine oil-contaminated sand.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, waste glass can be fully recycled in a conventional production process, but this is not an easy task due to the complexity of the cleaning, separation and sorting processes. For decades the academic community has been working hard to develop the use of waste glass in the production of building materials [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Almost eighty percent of 130 million tonnes of global production of glass each year are being discarded as waste while only 21% of the waste glass (WG) is recycled [1,2]. The waste glass has been investigated either as a substitution for binder (because of its pozzolanic properties) or as a replacement for aggregate in concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Ke et al showed that using waste glass with a particle size coarser than 300 µm and a substitution rate higher than 30% induces ASR expansion [4]. Siddika et al reported that the ASR expansion issue is less critical for geopolymers compared with conventional concrete [1,2].…”
Section: Introductionmentioning
confidence: 99%